Life cycle assessment of bio-based sodium poly-acrylate production from pulp mill side streams-Case at a TMP and sulphite pulp mill - Gontia, Paul (My University, 2014)
Sodium poly-acrylate is a super absorbent polymer which can be used in diverse hygiene products. The polymer is currently produced from fossil feedstock. The environmental issues and the depletion of fossil resources are the main drivers for exploring a more sustainable polymer product. Thus, integrating the production of the sodium-poly-acrylate in two different pulp mills (Ortviken pulp and paper mill in Sundsvall, and the Domsjö pulp mill in Örnsköldsvik) can potentially be a successful way to achieve sustainability. The main innovative part of the development is the conversion of the hemicellulose, derived from five diluted side streams into 3-hydroxypropionic (3-HP) acid by genetically modified yeasts developed at Chalmers. In order to reveal the environmental tradeoffs between renewable, bio-based and non-renewable, fossil based sodium poly-acrylate a comparative, cradle-to-gate life cycle assessment (LCA) was conducted. For bio-based polymers, forestry activities, pulp and paper mills operations, acrylic acid production (including: concentration, hydrolysis, and detoxification of the side streams; fermentation of the free sugars; recovery, dehydration and distillation of 3-HP), and the polymerization of acrylic acid were the production steps considered in this study. The goals of the LCA study were: 1) to compare the renewable, bio-based and non-renewable, fossil based production of sodium poly-acrylate; 2) to identify the environmental hotspots at a very early stage of the development. According to the results three of the bio-based polymers have a lower global warming potential (GWP) than the fossil-based polymer. However, the fossil-based polymer shows a lower environmental impact than its bio-based counterparts for three of the other environmental impact categories considered (acidification potential, eutrophication potential, and photochemical ozone creation potential). For the polymers produced at Ortviken, the concentration of the side streams is the hotspot identified. For the polymers produced at Domsjö, the hotspots identified are the detoxification, fermentation and recovery processes. Forestry activities, pulp mill operations, dehydration and distillation processes have very small contribution to the overall environmental impacts.
Keywords: Annan naturvetenskap; Other Natural Sciences